Designing an Educational Effectiveness Model for the Employees of the Selected Organization with a System Dynamics Approach - HajiAbedi, Sedigheh (2020)
The purpose of this research is to design an educational effectiveness model for the employees of the selected organization with a system dynamics approach in Iran. In order to achieve the research goal, a sequential mixed method has been used, which includes two qualitative and quantitative parts. In the qualitative part of the research, interview has been used. Necessary information and data were collected from experts and senior managers of the selected organization and then the design of the educational effectiveness model for the employees of the selected organization with a dynamic system approach has been validated. The research results showed that the educational effectiveness model for the employees of selected organization with a system dynamics approach has two parts: the main factors and their indicators. This model has been composed of indicators that are the core and heart of this model and are the basis for evaluating the educational effectiveness, which are called effective factors. The educational effectiveness model for the employees of the selected organization with a system dynamics approach has 7 main factors: learner's readiness, training need assessment, training targeting, training program design, resources and equipment allocation, course monitoring and evaluation and training course management, which includes 56 indicators composing it.